Рекомбiнацiйнi характеристики пластин монокристалiчного кремнiю з приповерхневим порушеним шаром - Sachenko, A. V.; Kostylyov, V. P.; Litovchenko, V. G.; Popov, V. G.; Romanyuk, B. M.; Chernenko, V. V.; Naseka, V. M.; Slusar, T. V.; Kyrylova, S. I.; Komarov, F. F. (Publishing house "Academperiodika", 2018)
Spectral dependences of the small-signal surface photovoltage, Vf (л), with a region of short- wave recession have been studied experimentally and theoretically. The dependences Vf (л) are shown to enable important information concerning a modification of surface and bulk recombination properties of the photosensitive silicon material in the short-wave spectral range to be obtained experimentally with the use of a nondestructive technique. In particular, theformation of a damaged near-surface layer owing to the Fe implantation is found to bring about a significant decrease in the diffusion length (i.e. the lifetime) in the implanted layer and an increase of the effective surface recombination rate on the illuminated surface.